2011
DOI: 10.5034/inquiryjrnl_48.03.03
|View full text |Cite
|
Sign up to set email alerts
|

Have Working-Age People with Disabilities Shared in the Gains of Massachusetts Health Reform?

Abstract: The Massachusetts health reform, implemented in 2006 and 2007, reduced the uninsurance rate for working-age people with disabilities by nearly half. Enrollment in Medicaid and subsidized insurance accounted for most of the gain in insurance coverage. The reduction in uninsurance was greatest among younger adults. The reform also reduced cost-related problems obtaining care; however, cost remains an obstacle, particularly among young adults with disabilities. The Massachusetts outcomes demonstrate that insuranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Various Affordable Care Act (ACA) provisions increase availability of coverage for young adults but there are reasons to be skeptical about the effectiveness of such reforms for transition age youth with substantial mental health morbidity. Studies of health care reform in Massachusetts found increased enrollment for young adults in Medicaid and healthcare exchanges (Gettens, Mitra, Henry, & Himmelstein, 2011; Long, Yemane, & Stockley, 2010) but worse enrollment among adults with behavioral health problems (Capoccia, Croze, Cohen, & O’Brien, 2013). The effects of ACA on health care coverage should be monitored among vulnerable youth.…”
Section: Policy and Practice Recommendationsmentioning
confidence: 99%
“…Various Affordable Care Act (ACA) provisions increase availability of coverage for young adults but there are reasons to be skeptical about the effectiveness of such reforms for transition age youth with substantial mental health morbidity. Studies of health care reform in Massachusetts found increased enrollment for young adults in Medicaid and healthcare exchanges (Gettens, Mitra, Henry, & Himmelstein, 2011; Long, Yemane, & Stockley, 2010) but worse enrollment among adults with behavioral health problems (Capoccia, Croze, Cohen, & O’Brien, 2013). The effects of ACA on health care coverage should be monitored among vulnerable youth.…”
Section: Policy and Practice Recommendationsmentioning
confidence: 99%
“…Each step of preventing disenrollment or obtaining alternative health care coverage requires individuals to engage in the application process, which may be a substantial barrier for this group. Indeed, studies of the Massachusetts health care reform have found increased enrollment for young adults in Medicaid and through health care exchanges, (41, 42) but worse enrollment among adults with behavioral health problems (43). …”
Section: Discussionmentioning
confidence: 99%
“…Our findings of increased OOP spending postreform concur with longer term findings for adults: although gaining insurance initially increased financial protection, many families and individuals have faced higher-than-expected OOP spending postreform. 23,45,[59][60][61][62] Because OOP spending increased in Massachusetts and other states for CSHCN, the increase may reflect a national trend toward decreased financial protection.…”
Section: Discussionmentioning
confidence: 99%